Redefining Violence for the Anthropocene: From Ecocide to Ecological Civilization - Ruuska, Toni; Heikkurinen, Pasi; LeVasseur, Todd; Arran Gare (Cosmos and History: The Journal of Natural and Social Philosophy, 2024)
TThe Anthropocene puts humanity within the continuum of long-running Earth processes, but what does it mean to be violent in deep time? This article aims to redefine violence for the Anthropocene. It does so by first examining the temporal dimensions of violence, where violence is claimed to be a historic and stratigraphic phenomenon, as much as it is present, immediate, and abrupt. Violence is relational, slow, and often accumulating, but there exists also violence that is stratigraphic, which bears the witness of and that will impact organisms and ecosystems other than us, the humans, in the distant future. Second, the article links violence to violation, and shows how violence is an evaluative term. In short, this means that violence should always be treated on a case-by-case basis. Third, the article posits that the notion of violence should be extended to the more-than-human world, as other beings, habitats, landscapes, and ecosystems can be, are, and have repeatedly been violated by human actions. Following these claims, the article proposes a non-anthropocentric definition of violence as encounters entailing the use of force that violates life-supporting processes. For reducing violence in ecosystems, the article calls for a withdrawal from the industrial-capitalist megamachine and placing more emphasis on the provisioning of fundamentals of life and other collective efforts advancing an ecological civilization